MEMBUMIKAN PLURALISME PERSPEKTIF ISLAM INDONESIA: FAKTA, TANTANGAN DAN GAGASAN - Mahathir Muhammad Iqbal (Postgraduate State Islamic Institute (IAIN) Metro, 2015)
Indonesia is a pluralistic nation. Both in terms of cultural entities, language, tribe, ethnic and religious differences. Therefore, the pluralism can not be understood simply by saying that our society is pluralistic, diverse, or made up of different tribes and religions, which is actually only describe the impression of fragmentation, not pluralism. Pluralism should also not be understood merely